Removal of patulin by thiol-compounds: A review. (15th January 2022) - Diao, Enjie; Ma, Kun; Qian, Shiquan; Zhang, Hui; Xie, Peng; Mao, Ruifeng; Song, Huwei
Abstract: Patulin (PAT) is a toxic mycotoxin usually contaminated apple juices, which leads to a serious food safety issue in the world. Thiol-compounds are a class of compounds containing the thiol (–SH) group themselves or obtained the –SH group by physical or chemical modification. They have the ability to efficiently remove patulin in apple juices with manifested negligible effects on juice quality. This review investigates the latest development in the removal of patulin using thiol-compounds, including the removal efficiencies and mechanisms of patulin, the factors influencing the removal efficiency of patulin, as well as the toxicities of thiol-compounds and safety of juices after detoxification. This review shows that thiol-compounds are promising materials for the removal or degradation of patulin in the contaminated juices. Graphical abstract: Image 1